Hippocampal antioxidative system in mesial temporal lobe epilepsy. (9th April 2015) - Ristić, Aleksandar J.; Savić, Danijela; Sokić, Dragoslav; Bogdanović Pristov, Jelena; Nestorov, Jelena; Baščarević, Vladimir; Raičević, Savo; Savić, Slobodan; Spasojević, Ivan
Summary Objective To examine antioxidative system in hippocampi of patients with mesial temporal lobe epilepsy associated with hippocampal sclerosis (mTLE‐HS). Methods Activity and levels of antioxidative enzymes—catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), manganese superoxide dismutase (MnSOD), and copper‐zinc superoxide dismutase (CuZnSOD)—were assessed in hippocampi of nine pharmacoresistant mTLE‐HS patients (mean age 37.7 ± [standard deviation] 6.6 years) who underwent amygdalohippocampectomy, and in 10 hippocampi obtained via autopsy from five neurologically intact controls (mean age 34.4 ± 9.0 years). Subfield and cellular (neuron/astrocyte) distribution of CAT, GPx, and MnSOD was analyzed in detail using immunohistochemical staining. Results Sclerotic hippocampi showed drastically increased activity of hydrogen peroxide–removing enzymes, CAT (p < 0.001), GPx (p < 0.001), and GR (p < 0.001), and significantly higher protein levels of CAT (p = 0.006), GPx (p = 0.040), GR (p = 0.024), and MnSOD (p = 0.004), compared to controls. CAT immunofluorescence was located mainly in neurons in both controls and HS. Control hippocampi showed GPx staining in blood vessels and CA neurons. In HS, GPx‐rich loci, representing bundles of astrocytes, emerged in different hippocampal regions, whereas the number of GPx‐positive vessels was drastically decreased. Neurons with abnormal morphology and strong MnSOD immunofluorescence were present in all neuronal layers in HS. Small autofluorescent deposits, most likely lipofuscin, were observed, along with astrogliosis, in CA1 in HS. Significance Antioxidative system is upregulated in HS. This documents, for the first time, that epileptogenic hippocampi are exposed to oxidative stress. Our findings provide a basis for understanding the potential involvement of redox alterations in the pathology of epilepsy, and may open new pharmacologic perspectives for mTLE‐HS treatment.